Charter of the City of Portland, Street and Fire Department Laws, Ordinances, Regulations &C., at 205-206, Concerning Offences and Disorderly Conduct, § 2 (1872) - (:unkn) unknown (My University, 1868)
That any person or persons who shall fire any pistol, gun or rifle, or any other species of fire-arms within the following limits: the Willamette river on the east and (10) Tenth Street on the west, Caruther's Addition on the south nd F Street on Couch's Addition on the north, shall on conviction thereof before the Recorder, be subject to a penalty of not less than five nor more than fifty dollars, or imprisonment, at the discretion of the Recorder, not exceeding twenty days. Provided that the Marshal shall permit upon the national holidays and other days of public celebration, any appropriate display of fire-arms and other instruments named in this section.]
Keywords: DISCHARGE